Paleohydrological Changes in Jura (France), and Climatic Oscillations around the North Atlantic from Allerød to Preboreal - Magny, Michel (Géographie physique et Quaternaire, 1995)
ABSTRACTRegional palaeohydroiogical changes recorded in the Jura lakes, France, have led to a tentative reconstruction of a fine-scale pattern of climatic changes from Allerød to the early Holocene. The Younger Dryas (YD) can be subdivided into three parts: after a first wet phase, this cool period was characterized by increasing dryness; a short rise in lake level developed during its last part. Moreover, the YD was preceded and followed by two short rises in lake-level, which interrupted the lake-level lowerings developing during the Allerød and the Preboreal. Climatic oscillations reconstructed in Jura appear to be in phase with glacier and tree-limit movements in the Alps, with fluctuations in oxygen-isotope records from the Swiss lakes and the Greenland ice sheet, and with climatic oscillations recorded in the Norwegian Sea. Other correlations between (1) these climatic oscillations, (2) 14C plateaux recorded in Swiss lake sequences, and (3) fluctuations in the residual ∆14C, support a correlation between regional palaeohydroiogical changes defined in Jura and broad-scale climatic oscillations; they also support the existence of a link between climatic changes in Western and Central Europe and oceanic circulation. Moreover, as working hypothesis, these correlations suggest high-precision timing for the climatic and environmental changes occurring during the early Holocene.